The Usage of Illustration for Material Perception Improvement in Studying Natural Disciplines - Bodnenko, Dmitriy; Radchenko, Sergej; Jurtin, Ivan (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article is devoted to university’s scientific research "Technology of implementation competent approach for future professionals’ training in multidisciplinary university" (KUBG). The research’s aim is generalizing of the analysis of illustrative material characteristics influence on the perception of the theoretical material by the students. The objects of the studying are science teaching, using of the illustrative material in the learning process. The test module and questionnaires were used in Moodle, system of distance learning. The features of representation about illustrative material during the science teaching were generalized. The most effective methods of illustrative material’s formation for improving the teaching of natural sciences were offered.